How Duterte States His View on The Philippines and Other Countries Relation: A Discursive Strategy Analysis - Andifa Chaerunnisa; Haru Deliana Dewi (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2019)
Different types of social or cultural background, combined with a region or social status, go into the making of spoken or written discourse. One of the interesting spoken discourses to discuss is political interview. It often reveals the intention of political leaders’ way of speaking. While there are those who are subtle in their way of talking, there are also a few who do not, one of whom is the Philippines’ president, Rodrigo Roa Duterte. Known for his outspoken personality, he often states controversial things that influence his country and derive critics from various places. Using van Dijk’s (2004) framework, this study analyzes the macro and micro discursive strategies used by Duterte in delivering his views on other countries’ relations with the Philippines based on his most-watched English interview with Russia Today. The findings revealed that the macro strategies used by Duterte are positive self-presentation, negative other-presentation, and outside polarization. Meanwhile, the mostly micro discursive strategies used are implication, lexicalization, and example/illustration.